Why is surgery not popular among medical students and young doctors? - Review of literature - Daniel, Piotr; Składanek, Justyna; Leśkiewicz, Michał; Otręba, Karina; Cieszkowska, Joanna; Czupryńska, Karolina (Journal of Education, Health and Sport, 2024)
Introduction: Contemporary medicine is witnessing significant advancements in conservative treatment modalities. However, surgery remains paramount for radical cancer treatment and emergent conditions such as trauma, peritonitis, gastrointestinal obstruction, and cholecystitis. Despite the essential role of surgeons, there is a global trend indicating waning interest among medical students in pursuing surgical specialties. Concurrently, practicing surgeons report heightened levels of professional burnout, and many regions face a looming shortage of surgical professionals, posing a threat to healthcare quality. Brief Overview of Current Knowledge: Research conducted across Poland, Germany, Argentina, the United Kingdom, and Japan highlights the declining inclination towards surgery among medical students. Students cite unattractive working conditions, poor work-life balance, elevated stress levels, and limited avenues for scholarly growth as deterrents. Gender plays a role, with females expressing heightened concerns regarding work-life balance and family aspirations. Furthermore, the surgical work environment, inadequate preparatory training in medical schools, and prolonged working hours are identified as factors exacerbating burnout risk among surgeons. Summary: Professional burnout represents a significant concern among surgeons, impacting both their work satisfaction and patient safety. Despite the strides made in conservative medical therapies, surgery remains indispensable, yet its allure as a specialty is diminishing among medical students. Understanding and addressing the discouraging factors, along with promoting healthy work practices, may mitigate burnout and encourage young physicians to consider surgical careers.